LANGUAGE AND EXPRESSION IN THE COMEDY - Yıldız KOCASAVAŞ (International Journal of Eurasia Social Sciences, 2017)
In comedy, the contribution of language, expression and local accents are very high, we cannot deny it. It’s best example in Turkish Literature is Traditional Folk Literature. (Karagöz, Orta Oyunu and Meddah) We can say that Karagöz, Orta Oyunu and Meddah are the most stunning examples of comedy in Traditional Folk Literature. In this study, we are gonna investigate the examples of this subject, and we are gonna start from the Traditional Folk Literature texts. We can see that in Traditional Turkish Folk Comedy, characters are taking attention with their speech features and specific words. Sometimes,this specific words causes misunderstanding and misquotation, and this misquotations can lead to bickerings. In Traditional Turkish Folk Literature, this bickerings are comedy’s itself. If we evaluate the opinions of other researchers, we can say that we can categorize the humour elements under some different titles. In Traditional Folk Literature texts, we can meet by chance with making use of possibilities of poetry, nursery rhymes, folk songs, proverbs and idioms, synonyms… Moreover, we can see that, there is a a lot of foreign words,‘mainly Arabic and Persian words.’ And there are some riddles and rhetorics for kids.